The Use of Instagram Content Marketing to Expand Market Reach for UMKM Singkong Cheese Argotelo Salatiga (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study aims to analyze the effectiveness of content marketing strategies through Instagram social media in increasing competitiveness and market reach in local food MSMEs. The case study was conducted at Argotelo Cheese Cassava MSME in Salatiga. The research method employed is descriptive qualitative with a case study approach, which involved observing digital marketing activities, conducting in-depth interviews with key stakeholders, reviewing digital documentation, and analyzing Instagram insight data. The results indicate that attractive and consistent visual content plays a significant role in boosting engagement and strengthening brand identity. By leveraging Instagram’s features, Argotelo Cheese Cassava MSME has been able to maintain audience interest and develop a strong online presence. The study also highlights the importance of content storytelling, audience response, and visual consistency as key elements in fostering long-term relationships with followers and customers. These factors contribute not only to increased customer loyalty but also to expanding the MSME’s market reach. Furthermore, the research reveals that data-driven decision-making in content creation, based on Instagram insights, allows the MSME to refine its strategies and engage its target market more effectively. The consistent use of high-quality images, informative captions, and timely interactions with the audience has proved beneficial in improving the MSME's visibility. In conclusion, a creative, consistent, and data-driven content marketing strategy on Instagram can significantly enhance the digital presence, visibility, and competitiveness of MSMEs, helping them to stand out in the competitive food industry market. This study contributes to understanding how local MSMEs can leverage social media platforms like Instagram to effectively compete and expand their market reach. Keywords: ; ;;;